Identifying Sources of Faecal Contamination in a Small Urban Stream Catchment: A Multiparametric Approach - Reynolds, Liam J.; Martin, Niamh A.; Sala-Comorera, Laura; Callanan, Kevin; Doyle, Padraig; O’Leary, Clare; Buggy, Paul; Nolan, Tristan M.; O’Hare, Gregory M. P.; O’Sullivan, John J.; Meijer, Wim G. (Frontiers in Microbiology, 2021)
Small urban streams discharging in the proximity of bathing waters may significantly contribute to the deterioration of water quality, yet their impact may be overlooked. This study focuses on the Elm Park stream in the city of Dublin that is subject to faecal contamination by unidentified sources. The aim of the study was to identify a minimum number of ‘sentinel’ sampling stations in the Elm Park stream that would provide the maximum amount of information regarding faecal pollution in the catchment. Thus, high-resolution sampling within the catchment was carried out over the course of one year at 11 stations. Faecal indicators bacteria were enumerated and microbial source tracking was employed to evaluate human pollution of the Elm Park Stream catchment. In addition, ammonia, total oxidised nitrogen, and phosphorus levels were monitored to determine if these correlated with faecal indicator and MST markers. In addition, the effect of severe weather events on water quality was assessed using automated sampling at one of the identified ‘sentinel’ stations during baseflow and high flow conditions over a 24-hour period. Our results show that the Elm Park stream is at times highly contaminated by point source faecal pollution and human faecal pollution is pervasive in the catchment. Correlations between ammonia concentrations and faecal indicator bacteria as well as the human MST marker were observed during the study. Cluster analysis identified four ‘sentinel’ stations that would provide sufficient information on faecal pollution in the stream, reducing the geographical complexity of the catchment. Furthermore, ammonia levels strongly correlated with faecal indicator bacteria and the human HF183 MST marker under high flow conditions at key ‘sentinel’ stations. Interestingly, the ammonium and nitrate levels during these conditions were inversely correlated, suggesting that ammonium levels may be a better indicator of recent human faecal contamination than nitrate levels. This work demonstrates the effectiveness of pairing microbial source tracking, faecal indicators and ammonium monitoring to identify ’sentinel’ stations that could be more rapidly assessed using real time ammonium readouts to assess remediation efforts.